2013
DOI: 10.1016/j.bbrc.2013.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Probing insect odorant receptors with their cognate ligands: Insights into structural features

Abstract: Oodorant receptors (ORs) are essential for insect survival in the environment and thus are ideal molecular targets for the design of insect-inspired modern green chemicals to control populations of agricultural pests and insects of medical importance. Although insect ORs are known for more than a decade, their structural biology is still in its infancy. Here, we unravel the first structural features of ORs from the malaria mosquito, the Southern house mosquito and the silkworm moth. The second extracellular lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 40 publications
3
33
0
Order By: Relevance
“…There are experimental evidences that mutations in TM2, 3 and 4 domains affect ligand binding in Drosophila, mosquito or moth receptors (Nichols and Luetje, 2010;Pellegrino et al, 2011;Leary et al, 2012;Hughes et al, 2014) whereas mutations in TM5, 6 and 7 affect the ion channel function of a moth PR (Nakagawa et al, 2012). An in silico analysis of insect OR structural features also identified N-ter, EL2 and IL3 domains as the most evolutionary constrained (Hopf et al, 2015), which is consistent with their importance for the correct functioning of ORs (Benton et al, 2006;Jin et al, 2008;Xu and Leal, 2013). Further experimental validations are needed to confirm whether positive selection has indeed been a driving force for the diversification of moth PRs or not.…”
Section: Discussionmentioning
confidence: 51%
“…There are experimental evidences that mutations in TM2, 3 and 4 domains affect ligand binding in Drosophila, mosquito or moth receptors (Nichols and Luetje, 2010;Pellegrino et al, 2011;Leary et al, 2012;Hughes et al, 2014) whereas mutations in TM5, 6 and 7 affect the ion channel function of a moth PR (Nakagawa et al, 2012). An in silico analysis of insect OR structural features also identified N-ter, EL2 and IL3 domains as the most evolutionary constrained (Hopf et al, 2015), which is consistent with their importance for the correct functioning of ORs (Benton et al, 2006;Jin et al, 2008;Xu and Leal, 2013). Further experimental validations are needed to confirm whether positive selection has indeed been a driving force for the diversification of moth PRs or not.…”
Section: Discussionmentioning
confidence: 51%
“…Consistent with other moths (Bengtsson et al, 2012;Feng et al, 2015;Zhang et al, 2013Zhang et al, , 2015, the AlepORco gene also displayed a very high mRNA abundance. Many previous studies showed that ORco could act as a chaperone and dimerization partner for other ORs, forming a ligand gated ion channel to specific ligands (Krieger et al, 2003(Krieger et al, , 2005Nakagawa et al, 2005;Xu and Leal, 2013), and ORco was more highly conserved in insects than other ORs (Krieger et al, 2003;Leal, 2013;Robertson et al, 2003;Vogt, 2005), thus it required more ORco transcripts to activate different ORs. In addition, we identified 4 candidate PR genes by sex expression and physiologic analysis.…”
Section: Discussionmentioning
confidence: 98%
“…Antennae and legs dissected from blood-fed adult females were used for RNA-Seq as well as to generate templates for validation by qPCR and gene cloning. Deorphanization of a unique OR gene was performed with the Xenopus oocyte expression system (9,35). Oocytes expressing CquiOR95b along with CquiOrco were challenged with large panel of physiologically relevant odorants.…”
Section: Methodsmentioning
confidence: 99%